Determination of mode II cohesive law of bovine cortical bone using direct and inverse methods. (April 2018) - Pereira, F.A.M.; de Moura, M.F.S.F.; Dourado, N.; Morais, J.J.L.; Xavier, J.; Dias, M.I.R.
Highlights: The cohesive law of cortical bone under mode II loading is obtained using ENF tests. Two methods were used to determine the cohesive law: direct (DM) and inverse (IM). Strain energy release rate is correlated with crack tip shear displacement (CTSD). The DM uses the differentiation of strain energy release rate with respect to CTSD. The IM uses FEA with cohesive zone modeling associated with optimization algorithm. Abstract: This study presents two alternative methods to determine the cohesive law of bovine cortical bone under mode II loading, employing the End Notched Flexure (ENF) test. The direct method results from the combination of the progress of the mode II strain energy release rate with the crack tip shear displacement, obtained by digital image correlation. The resulting cohesive law is determined by differentiation of this relation relatively to the crack shear displacement. The inverse method employs finite element analyses with cohesive zone modelling, in association with an optimization procedure. The resulting strategy enables determining the cohesive law without establishing a pre-defined shape. The significant conclusion that comes out of this work is that both methods offer consistent results regarding the estimation of the cohesive law in bone. Given that the inverse method dispenses the use of sophisticated equipment to obtain the cohesive law in bone, it can be used as a more convenient procedure to accomplish efficient studies in the context of bone fracture characterization under mode II loading. Graphical abstract: Image, graphical abstract